Forecasting Healthy Life Expectancy Among Chilean Community-Dwelling Older Adults With and Without Sarcopenia - Moreno, Ximena; Lera, Lydia; Márquez, Carlos; Albala, Cecilia (Frontiers in Medicine, 2022)
Background: Sarcopenia is an important risk factor for disability and dependency at old age. The prevalence of sarcopenia among the Chilean older population is high. Objective: To estimate life expectancy, healthy life expectancy and unhealthy life expectancy among sarcopenic and non-sarcopenic older adults from Santiago, Chile. Methods: A sample of 1897 community-dwelling older adults aged 60 years or more, living in Santiago, was observed between 5 to15 years. Disability was defined as the unhealthy state, assessed through self-reported difficulties in activities of daily living. Sarcopenia was determined via HTSMayor software. Total and marginal life expectancies were estimated using the Interpolated Markov Chain method "IMaCh". Results: At 60 years, estimated life expectancy for sarcopenic and non-sarcopenic older adults was similar (22.7 and 22.5 years, respectively). The proportion of years to be lived with disability was three times greater in sarcopenic adults, compared to non-sarcopenic people. This difference was observed up to 80 years. Non-sarcopenic women had a higher proportion of years to be lived with disabilities compared to non-sarcopenic men of the same age, but this proportion was higher among sarcopenic men, compared to sarcopenic women until 70 years of age. Discussion: People with sarcopenia expect to live a higher proportion of years with disabilities. Sarcopenic men until 70 years expected to live a higher proportion of years with disability, compared to sarcopenic women. Monitoring sarcopenia among older people may help to identify individuals with higher risk of disability onset. Future research should focus on disentangling the mechanisms explaining sex differences.